Methane partial oxidation by the lattice oxygen of the lanio₃δ perovskite. a pulse study (2010)
LaNiO₃ perovskite was prepared by the selfcombustion method and tested as catalyst for CH4 activation using the oxygen lattice at 700°C and 800°C. Based on the non-stoichiometry experiments, the perovskite formula is written as La³⁺+ Ni³⁺ 0.37Ni²⁺ 0.63O2.68. When unreduced LaNiO3d perovskite is used, only type oxygen species were responsible for the partial CH₄ oxidation. Over non reduced perovskite high CH4 conversions to H₂ and CO were obtained. CH4 conversion and H₂, CO and CO₂, selectivities under quasistationary conditions were 100%, 80%, 98% and 2 % respectively at 800°C. At the beginning of the reaction, a complete oxidation of methane to CO₂ and H₂O took place, whereas a partial oxidation to CO and H₂ was observed after that period. In such conditions the H₂/CO molar ratio obtained was 1.7, indicating a contribution of the parallel reverse water gas shift reaction